The relationship between coping strategies and psychological distress in Chinese older adults with multiple chronic conditions. (23rd March 2021) - Cheng, Cheng; Inder, Kerry; Chan, Sally Wai‐chi
Abstract: Objective: To examine the relationship between socio‐demographic and clinical variables, physical function, coping strategies and symptoms of anxiety and depression in Chinese older adults with multiple chronic conditions (MCCs). Methods: A secondary analysis of data from a prior cross‐sectional survey investigated coping and mental health among adults with multiple chronic conditions living in China. A convenience sample of 185 adults with MCCs was recruited from a university‐affiliated hospital between November 2017 and May 2018 in Northern Anhui, China. Results: Of the 185 participants, 63% of participants had scores indicating symptoms of anxiety and 54% had scores indicating depression. Stepwise regression models explained 47% of the total variance for the levels of anxiety and 34% for the levels of depression. In the anxiety model, gender, body pain, physical functioning, positive adaptation, denial and disengagement coping, and spiritual coping showed significant associations. In the depression model, gender, physical functioning, positive adaptation and spiritual coping showed significant associations. Conclusions: This study demonstrates the need to screen for anxiety and depression among older adults with MCCs. Individualised interventions that address coping strategies should be encouraged to maintain psychological well‐being in this population.